Characterization on mosaic glass found at Phu Khao Thong, southern area of Thailand - K. Won-In (2018)
Glasses in forms of ornament and decorative objects have been found in Thailand for several hundred years. The mosaic glass used in this work was only one piece that excavated at Phu Khao thong archaeological site in Ranong Province, southern area of Thailand. Micro-beam X-ray fluorescence spectroscopy (μ-XRF) based on synchrotron radiation was firstly carried out to analyze its elemental composition and distribution. Scanning electron microscope coupled with energy dispersive X-ray fluorescence spectroscopy (SEM-EDS) and (PIXE) were also used to characterize the composition. The main composition of this mosaic glass sample found in Thailand was a lead-based silicate glass. The colorations were affected from transition metals, especially iron, copper and manganese. It was shown that although it look-liked the same, but the main composition was differ to that of Persia and South Asia, especially the lead content. However, it demonstrated the long distance trade or exchange network of the ancient time.